(untitled) (Research, Society and Development, 2020)
This work exploratory analyzes the sustainability of the Sociedad Agrícola e Industrial San Carlos, S.A., which is a leading sugarcane company in Ecuador. An analysis of the indicators that are reported in their annual reports in the period 2012 - 2019 was carried out. It is observed that it is a company where there is evidence of an effort to comply with global environmental certification standards, which is why they passed from the report of reports or wide-ranging social balance sheets [2012 to 2015] to assume the Global Reporting Initiative (GRI) methodology in its Essential option [2016-2019], where the economic, environmental and social dimensions are analytically addressed. The Indices of Economic Responsibility (IRe), Environmental Responsibility (IRa) and Social Responsibility (IRs) reflect stages that vary from intermediate to mature sustainability, which reflects a systematic effort of good practices. The hypothesis contrast regarding the use of the two methodologies (W-Wilcoxon) indicates that the GRI 200 Economic standards (-2.475; p-value 0.00), as well as the GRI 300 Environmental (-2.618; p-value 0.00) and GRI 400 Social (-2.574; p-value 0.00), present a significant difference that indicates that the valuations obtained with the use of GRI in the years 2016-2019 are significantly higher compared to the Social Balance approach. It is highlighted that the use of the GRI methodology has contributed to an improvement and increase in the indicators or thematic contents, which supports its adoption; therefore it represents an evolutionary leap for the sustainability of the company.